Direct investigations of deformation and yield induced structure transitions in polyamide 6 below glass transition temperature with WAXS and SAXS. (23rd July 2015) - Guo, Huilong; Wang, Jiayi; Zhou, Chengbo; Zhang, Wenyang; Wang, Zixuan; Xu, Bihui; Li, Jingqing; Shang, Yingrui; de Claville Christiansen, Jesper; Yu, Donghong; Wu, Zhonghua; Jiang, Shichun
Abstract: Deformation and yield induced structure transitions of polyamide 6 (PA6) were detected with the combination of the wide- and small-angle X-ray scattering (WAXS and SAXS) at 30 °C below glass transition temperature (Tg ) of PA6. During deformation, γ-α phase transition was found at elastic stage. The concentrated stress in crystals at elastic stage provided adequate energy for the direct γ-α phase transition under Tg . The force to promote the γ-phase into α phase directly is insufficient at the yield stage and a transient phase as a compromise was formed. The transient phase was confirmed by DSC measurements and assisted the γ-α phase transition indirectly. The γ-phase slips into incomplete fragments at yield point, and the parts along tensile direction are responsible for the formation of transient phase. The γ-fragments after yield is oriented by shear force following α-phase. The yield of PA6 was intimately related with the γ-transient phase transition and the slippage of γ-fragments. In addition, the increase of long spacing at elastic deformation along tensile direction was mainly contributed by the amorphous region. After yield, the phase transition and crystalline slippage affected the lamellar evolution. A simplified schematic diagram was provided to illustrate the structure evolution of PA6. Graphical abstract: Direct investigations of deformation and yield induced structure transitions in polyamide 6 below glass transition temperature with WAXS and SAXS. Highlights: By using the combination of the WAXS and SAXS techniques on bulk PA6 during uniaxial drawing, a transient crystalline stage in the course of the γ-α strain-induced phase transformation was observed at 30 °C (below Tg ). The γ-phase slips into incomplete fragments at yield point, and the parts along tensile direction are responsible for the formation of transient phase. A simplified schematic diagram was provided to illustrate the structure evolution of PA6.